Long-Term Immunogenicity and Safety of a Homologous Third Dose Booster Vaccination with TURKOVAC: Phase 2 Clinical Study Findings with 32-Week Post-Booster Follow-Up - Zafer Sezer; Shaikh Terkis Islam Pavel; Ahmet Inal; Hazel Yetiskin; Busra Kaplan; Muhammet Ali Uygut; Ahmet Furkan Aslan; Adnan Bayram; Mumtaz Mazicioglu; Gamze Kalin Unuvar; Zeynep Ture Yuce; Gunsu Aydin; et al. (Vaccines, 2024)
Vaccine-induced immunity wanes over time and warrants booster doses. We investigated the long-term (32 weeks) immunogenicity and safety of a third, homologous, open-label booster dose of TURKOVAC, administered 12 weeks after completion of the primary series in a randomized, controlled, double-blind, phase 2 study. Forty-two participants included in the analysis were evaluated for neutralizing antibodies (NAbs) (with microneutralization (MNT50) and focus reduction (FRNT50) tests), SARS-CoV-2 S1 RBD (Spike S1 Receptor Binding Domain), and whole SARS-CoV-2 (with ELISA) IgGs on the day of booster injection and at weeks 1, 2, 4, 8, 16, 24, and 32 thereafter. Antibody titers increased significantly from week 1 and remained higher than the pre-booster titers until at least week 4 (week 8 for whole SARS-CoV-2) (p < 0.05 for all). Seroconversion (titers ≥ 4-fold compared with pre-immune status) persisted 16 weeks (MNT50: 6-fold; FRNT50: 5.4-fold) for NAbs and 32 weeks for S1 RBD (7.9-fold) and whole SARS-CoV-2 (9.4-fold) IgGs. Nine participants (20.9%) tested positive for SARS-CoV-2 RT-PCR between weeks 8 and 32 of booster vaccination; none of them were hospitalized or died. These findings suggest that boosting with TURKOVAC can provide effective protection against COVID-19 for at least 8 weeks and reduce the severity of the disease.